2021
DOI: 10.1088/1402-4896/abd654
|View full text |Cite
|
Sign up to set email alerts
|

Quantum phase diagrams of matter-field Hamiltonians II: Wigner function analysis

Abstract: Non-classical states are of practical interest in quantum computing and quantum metrology. These states can be detected through their Wigner function negativity in some regions. We show that the surfaces of minimum fidelity or maximum Bures distance constitute a signature of quantum phase transitions. Additionally the behaviour of the Wigner function associated to the field modes carry the information of both, the entanglement properties between matter and field sectors, and the regions of the parameter space … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…gapped. The Goldstone mode also appear in the so called SU (3) Dicke model [912][913][914]. Here the two boson modes couple to SU (3) pseudo-spins, e.g.…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…gapped. The Goldstone mode also appear in the so called SU (3) Dicke model [912][913][914]. Here the two boson modes couple to SU (3) pseudo-spins, e.g.…”
Section: The Dicke and Tavis-cummings Modelsmentioning
confidence: 99%
“…Another criterion that we have proposed [1,2] in order to find transitions not detectable through the Ehrenfest classification, is to use the Bures distance in the total product space of n-level atoms and -mode radiation field, defined by [20,21]…”
Section: Three-level Atomsmentioning
confidence: 99%
“…As a general procedure, one selects various points around a circumference of radius ε about each point p in parameter space, in order to find the state with maximum distance to p (cf. [1,2] for details). In our case, it was sufficient to calculate it for four points about each p in order to get a qualitative behavior of the surface of maximum Bures distance.…”
Section: Three-level Atomsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an alternative formulation of quantum mechanics, phase space methods have numerous applications in many areas of physics, e.g., quantum optics [18], atomic physics [19,20], quantum chaos [21,22], condensed matter physics [23,24], and quantum thermodynamics [25][26][27]. In particular, recent studies have shown that phase space methods are a powerful tool for the understanding of quantum phase transitions in many-body systems [28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%